Reliability and Responsiveness of Gait Speed, Five Times Sit to Stand, and Hand Grip Strength for Patients in Cardiac Rehabilitation - Puthoff, Michael L. (Cardiopulmonary Physical Therapy Journal, Inc., 2013)
PURPOSE: Following a cardiac event patients are at risk for deficits in mobility and function. However, measures of physical performance are not commonly used and have not been extensively studied in patients enrolled in cardiac rehabilitation. The purpose of this study was to determine the reliability and the minimal detectable change (MDC) of gait speed, 5 times sit to stand (5 STS) and hand grip strength for individuals enrolled in cardiac rehabilitation. METHODS: Forty-nine individuals enrolled in phase II or III cardiac rehabilitation participated in the study. Gait speed, 5 STS, and hand grip strength were measured over two sessions held on the same day. Intraclass correlation coefficient was used to determine reliability and MDC(95) was calculated to measure responsiveness. RESULTS: All 3 measures showed high reliability (ICC for gait speed = 0.96, 5 STS = 0.87, right hand grip strength = 0.97, left hand grip strength = 0.97). The MDC(95) for gait speed was 0.16 meters/second, 3.12 seconds for 5 STS, 5.2 kilograms for right and 5.1 kilograms for left hand grip strength. CONCLUSION: Gait speed, 5 STS, and hand grip strength are reliable and responsive measures for patients in cardiac rehabilitation. Findings support their use in clinical practice and future cardiac rehabilitation studies.